COMPARATIVE OF COMPANY PROFITABILITY BEFORE AND AFTER THE COVID-19 PANDEMIC IN RETAIL COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Hartato Rianto; Agung Purnomo Sidik; Anita Putri (Proceeding International Seminar of Islamic Studies, 2022)
This study was conducted to determine how financial performance in retail companies listed on the Indonesia Stock Exchange before and after the Covid-19 pandemic. The data used was secondary data obtained from the official website of the Indonesia Stock Exchange at www.IDX.co.id. The data used were in 2019 and 2020. The population in this research were 25 retail companies with 18 companies as the sample. The profitability ratios tested and compared were Gross Profit Margin (GPM), Operating Profit Margin (OPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The method used was the Paired Sample T-Test with the help of the SPSS Version 24.0 application. The results showed that Gross Profit Margin (GPM), Operating Profit Margin (OPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) had no significant differences before and after the Covid pandemic. -19. The correlation results showed that only Gross Profit Margin (GPM) had a substantial relationship before and after the Covid-19 pandemic. In contrast, Operating Profit Margin (OPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) had no significant relationship before and after the Covid-19 pandemic.Keywords: Gross Profit Margin, Operating Profit Margin, Net Profit Margin, Return on AssetsReturn on Equity, Covid-19